2008
DOI: 10.2174/157015908787386113
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology and Therapeutic Potential of Sigma1 Receptor Ligands

Abstract: Sigma (σ) receptors, initially described as a subtype of opioid receptors, are now considered unique receptors. Pharmacological studies have distinguished two types of σ receptors, termed σ1 and σ2. Of these two subtypes, the σ1 receptor has been cloned in humans and rodents, and its amino acid sequence shows no homology with other mammalian proteins. Several psychoactive drugs show high to moderate affinity for σ1 receptors, including the antipsychotic haloperidol, the antidepressant drugs fluvoxamine and ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
300
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(313 citation statements)
references
References 208 publications
(347 reference statements)
6
300
0
7
Order By: Relevance
“…This indicates a competitive interaction between PRE-084 and both sigma-1 antagonists. These results agree with the pharmacological profile of these drugs, as it is known that PRE-084, BD-1063, and S1RA bind to sigma-1 receptors (17,20).…”
Section: Effects Of Sigma-1 Antagonists On Acute Inflammatory Hyperalsupporting
confidence: 89%
See 1 more Smart Citation
“…This indicates a competitive interaction between PRE-084 and both sigma-1 antagonists. These results agree with the pharmacological profile of these drugs, as it is known that PRE-084, BD-1063, and S1RA bind to sigma-1 receptors (17,20).…”
Section: Effects Of Sigma-1 Antagonists On Acute Inflammatory Hyperalsupporting
confidence: 89%
“…We tested the effects of the sigma-1 antagonists BD-1063 and S1RA (17,20) and the sigma-1 agonist PRE-084 (20). The opioid antagonists used were the centrally penetrant naloxone hydrochloride and its peripherally restricted analog naloxone methiodide (18).…”
Section: Methodsmentioning
confidence: 99%
“…Antagonists do not affect Ca 2+ release when given alone, but they impede the potentiation of Ca 2+ efflux by sigma-1 receptor agonists. After [13,40]. (For interpretation of the references to color in this figure legend, the reader is referred to the web version of the article.)…”
Section: Acetylcholine and Sigma-1 Receptor Functionmentioning
confidence: 99%
“…σ 1 Receptors have a neuromodulatory role on the neurotransmitter system, including the serotonergic, noradrenergic, dopaminergic, glutamatergic, and cholinergic systems, and are related to depression. [145][146][147][148][149][150][151] Previous studies using in vivo microdialysis showed that fluvoxamine causes a transient increase in the extracellular levels of DA and/or NA in the prefrontal cortex, 137,152,153) but it is not known whether σ 1 receptors are involved in the neurochemical effect of fluvoxamine.…”
Section: Modulation Of Prefrontal Da Release By Interaction Of the 5-mentioning
confidence: 99%